The antimicrobial action of resveratrol against Listeria monocytogenes in food-based models and its antibiofilm properties - Ferreira, Susana (2020)
BACKGROUND Resveratrol (3,5,4′‐trihydroxy‐trans‐stilbene) is a natural phytoalexin synthesized by plants in response to stress. This compound has several beneficial documented properties, namely anti‐inflammatory, antioxidant, neuroprotective and antimicrobial activities. In this study the antimicrobial activity of resveratrol against Listeria monocytogenes and Listeria innocua was investigated. RESULTS Resveratrol had a minimum inhibitory concentration of 200 µg mL−1 for the tested strains, with time‐kill curves demonstrating bacteriostatic activity. Inhibition of biofilm formation was also assessed, with resveratrol strongly inhibiting biofilm formation by both species even at subinhibitory concentrations. Overall, resveratrol showed antimicrobial properties on planktonic cells and on biofilm formation ability. Considering the potential use of resveratrol as a food preservative, the antimicrobial efficacy of resveratrol in food was studied in milk, lettuce leaf model and chicken juice. Resveratrol retained greater efficacy in both lettuce leaf model and chicken juice, but milk had a negative impact on its antilisterial activity, indicating a possible reduction of resveratrol availability in milk. CONCLUSION This study reinforces resveratrol as an antimicrobial agent, pointing out its antibiofilm activity and its potential use as preservative in some food matrices. © 2016 Society of Chemical Industry